C = x(x - y + 1) - y(y + 1 - x) tại x = -2/3; y = -1/3
C = x2 - xy + x - y2 - y + xy
C = (x2 - y2) + (x - y)
C = (x - y)(x + y) + (x - y)
C = (x - y)(x + y + 1)
Thay x và y vào C ta dc:
C = \(\left(\frac{-2}{3}-\frac{-1}{3}\right)\left(\frac{-2}{3}+\frac{-1}{3}+1\right)\)
C = \(\frac{-1}{3}\) . 0
C = 0
Tính : C= x(x-y+1)-y(y+1-x)tại x =-2/3;y=-1/
Ta có : C = x(x-y+1) -y(y+1-x) = \(x^2-xy+x\)- \(y^2-y+xy\)
= \(x^2-y^2+x-y\)
= \(\left(x-y\right)\left(x+y\right)+x-y\)
= \(\left(x-y\right)\left(1+x+y\right)\)
Thay x = -2/3, y = -1 ta có:
C = ( -2/3 - 1 )( 1 + ( -2/3) + (-1))
C = -5/3 . (-2/3)
C = 10/3
Vậy C = 10/3 khi x = -2/3 và y = -1
Do mik viết thiếu đề bài nên tính ra kết quả khác, sr